Lean information streams for an efficient ptoduction Schlanke Informationsflüsse für eine effiziente Produktion - Risch, Florian; Berndt, Rüdiger; Franke, Jörg (Zeitschrift für wirtschaftlichen Fabrikbetrieb, 2011)
Lean Information Processes for Efficient Production Systems. The increasing complexity in production related digital models - resulting from increasingly interconnected and globalized markets - results in a rising importance of data quality. The consequences - non-transparent and non-integrated communication and information processes - will be worsened by the use of simultaneous engineering approaches and grown, heterogeneous system landscapes. Moreover, the adaptability of the IT-structures to new situations in the highly dynamic production environments has become more difficult. The affected information processes are maintained through manual intervention and supposedly temporary solutions. This article discusses approaches for integrated and sustainable information and communication processes to ensure a high data quality. The method Value Stream Mapping was adapted for analysis and optimization of information processes. Furthermore, using standardized forms of a provision of data allows an implementation of stable information processes to support assembly work in future dynamic market environments.
CRIS-Team Scopus Importer:2024-08-06